A face feminina kalunga frente ao modelo de desenvolvimento nacional: a condução do licenciamento ambiental da PCH Santa Mônica no sítio histórico da comunidade quilombola Kalunga - Muniz, Izadora Nogueira dos Santos (2020)
Based on the interest of the company RIALMA, a private group that operates in the energy, agriculture and mining segments, owned by the Caiado, a family with permanent activities among politicians and ruralists in Goiás, who are applying for a Prior License for the implementation of a Small Hydroelectric Power Plant - called Santa Monica - within the territory of the Quilombola Kalunga Community, located in the State of Goiás, the work addresses, through interviews, procedural and jurisprudential analysis, the Kalungas female experiences and trajectories as a guiding thread to debate national development, which is based on the energy matrix hydroelectricity. Faced with this project, which presents itself as a possibility of "progress" and "development", in the company's discourse, conflicts emerge in which the perspective of Kalungas quilombola women demands greater attention, both because they belong to a group that needs specific rights and collectives (traditional / tribal peoples), as well as because historiography promotes an erasure of the performance of women in the trajectories of quilombos, which is particularly serious, as, as a rule, they encounter greater obstacles to the recomposition of their means and modes of when they are directly affected by national and regional development plans and programs. Also, in order to understand the processing of the Administrative Environmental Licensing Process No. 257/2008, which is currently being processed by the State Secretariat for the Environment and Sustainable Development of the State of Goiás, in addition to interviewees members of the Quilombo Association Kalunga and female leaders recognized by the Kalunga Community, also interviewed the legal advisor Kalunga who works within the National Coordination of Articulation of Black Rural Quilombola Communities, as well as employees of the Palmares Cultural Foundation and the National Institute of Colonization and Agrarian Reform. Based on the study, the research concluded that the coloniality of power and the coloniality of gender constitute a serious obstacle to the realization of the rights of the Kalunga people, showing structural racism and its institutional and socio-environmental developments.